FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN BODY LOTION EKSTRAK ETANOL DAUN KEMANGI (Ocimum cannum Sims.) DENGAN METODE DPPH (1,1 – diphenyl-2- picrylhydrazyl) - Yani Ambari; Arlin Oscardini Saputri; Iif Hanifa Nurrosyidah (As-Syifaa Jurnal Farmasi, 2021)
Basil leaves (Ocimum cannum Sims.) Are known to contain alkaloids, flavonoids, saponins, tannins, polyphenols, and triterpenoids. One of the compounds contained in the basil leaves (Ocimum cannum Sims.) Is a flavonoid which has antioxidant activity. Compounds that have antioxidant activity are known to prevent premature aging. This study aims to determine that the ethanol extract of basil leaves (Ocimum cannum Sims.) Can be formulated into Body Lotion with good physical stability or stable and to determine the antioxidant activity of Body Lotion ethanol extract of basil leaves (Ocimum cannum Sims.). The ethanol extract of basil leaves (Ocimum cannum Sims.) Was obtained by remaseration method using ethanol 96% with a yield percentage of 7.09%. Body lotion ethanol extract of basil leaves (Ocimum cannum Sims.) Is made in 3 formulas, which contain extracts F1 (0.5%), F2 (1%), and F3 (1.5%). Body lotion preparations were also tested for physical stability using the cycling test which included organoleptic, homogeneity, pH, dispersal, and adhesion tests. Then proceed to the determination of antioxidant activity carried out by the DPPH free radical reduction method by calculating the IC50 value. The results showed that the ethanol extract of basil leaves (Ocimum cannum Sims.) Has antioxidant activity with IC50 value of 7.05 ppm with AAI value of 14.1 and body lotion preparations can be made. The results of the body lotion antioxidant activity test of basil leaves ethanol extract (Ocimum cannum Sims.) Showed that, F3 had the strongest antioxidant activity namely IC50 18.36 ppm with AAI value of 11.9 then followed by F2 namely IC50 25.2 ppm with AAI value 3.9, and F1, namely IC50 90.5 ppm with AAI value of 14.1. Based on the research results obtained, it can be concluded that the higher the concentration of ethanol extract of basil leaves (Ocimum cannum Sims.) Added, the antioxidant activity of the body lotion will be stronger